Association of Thyroid Profile in Chronic Liver Disease: A Cross-Sectional Study at a Tertiary Care Center in Bareilly - Dr. PotrickFaizan Jalal; Dr. Mudassir Hussain; Dr. KP Singh; Dr. Mahipalpuri Singh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic liver disease (CLD) significantly impacts thyroid hormone metabolism. The interplay between hepatic dysfunction and thyroid abnormalities can affect prognosis. Aim: To assess the thyroid profile in patients with CLD and correlate thyroid function with liver disease severity. Methods: This cross-sectional study included 94 CLD patients. Thyroid function tests (T3, T4, TSH) and liver function tests were analyzed. Child-Pugh scores were calculated to grade disease severity. Results: A significant proportion of patients showed altered thyroid profiles, with low T3 syndrome being the most common abnormality. T3 levels inversely correlated with Child-Pugh scores, indicating that thyroid dysfunction worsened with liver disease progression. Conclusion: Thyroid dysfunction, particularly low T3 syndrome, is common in CLD and correlates with disease severity. Routine thyroid evaluation in CLD patients may improve clinical outcomes.